Can Behavioral Health Improve Without Social Workers? Insights from a Systematic Literature Review on Integrated Health Promotion - Chandra Kartika Dewi; Mahadna Aulia Rahmah; Berlinda Putri Nurrochayati (UIN Sunan Kalijaga Yogyakarta, 2025)
Various studies highlight health problems influenced by social factors, underscoring the need for integrated health promotion involving interprofessional roles. This study aims to identify the role of social workers in health promotion by reviewing behavioral health issues that significantly impact physical health. A systematic literature review was conducted, collecting 518 articles, with 27 selected based on inclusion criteria. These articles, published between 2015 and 2025 in PubMed and Scopus, underwent peer review. The articles were analyzed using the PICO framework, with searches based on the keywords “health-promoting universities,” “social work,” and “behavioral health.” The findings indicate that self-promotion, expert-led health promotion, and the contributions of health workers are key actors in addressing health issues tied to social determinants. These actors play critical roles in tackling mental health challenges, lifestyle risks, and social health concerns. This identification highlights opportunities for social workers to provide counseling, offer psychosocial support, enhance quality of life through empowerment, and foster community development. These roles represent the primary domain for social workers to actively contribute to integrated health promotion through interprofessional collaboration. Keywords: Health promotion, Social work, Behavioral health Problem kesehatan yang di determinasi oleh faktor sosial yang ditemukan dalam beragam penelitian mengindikasikan kebutuhan terhadap promosi kesehatan terpadu yang melibatkan peran antar profesi. Penelitian ini bertujuan untuk menemukan domain dari pekerja sosial dalam kontribusinya pada aspek promosi kesehatan dengan meninjau problem kesehatan perilaku yang banyakdiidentifikasi sebagai faktor yang mempengaruhi kesehatan fisik. Penelitian ini menggunakan systematis literature review dengan mengumpulkan 518 artikel dengan 27 artikel terpilih yang memenuhi kriteria. Artikel yang dipilih dalam penelitian ini telah dilakukan tinjauan sejawat dan diterbitkan antara tahun 2015 hingga 2025 dalam PubMed dan Scopus. Artikel diproses melalui kerangka PICO dengan menggunakan model penelusuran berdasarkan kata kunci health-promoting universities,” “social work,” and “behavioural health”. Penelitian ini menemukan bahwa self-promotion, promosi kesehatan melalui tenaga ahli, dan peran tenaga kesehatan merupakan aktor yang melakukan promosi kesehatan untuk mengatasi problem kesehatan yang berhubungan dengan dimensi sosial. Peran para aktor ini dianggap sebagai petugas yang memberikan solusi untuk menyelesaikan problem kesehatan mental, risiko gaya hidup, dan kesehatan sosial. Identifikasi ini memberikan ruang bagi para pekerja sosial dalam upaya memberikan konseling dan dukungan psiko-sosial, peningkatan kualitas hidup melalui pemberdayaan, dan pengembangan komunitas. Peran ini merupakan domain utama pekerja sosial untuk terlibat aktif dalam promosi kesehatan terpadu dengan melibatkan peran antar profesi.Kata Kunci: Promosi kesehatan, Pekerja sosial, Kesehatan perilaku